Fast X‐ray reflectivity measurements using an X‐ray pixel area detector at the DiffAbs beamline, Synchrotron SOLEIL. (18th December 2017) - Mocuta, Cristian; Stanescu, Stefan; Gallard, Manon; Barbier, Antoine; Dawiec, Arkadiusz; Kedjar, Bouzid; Leclercq, Nicolas; Thiaudiere, Dominique
Abstract : A method for rapid measurement of X‐ray reflectivity using an area detector and a monochromatic X‐ray beam, combined with a continuous data acquisition mode during the angular movements of the sample and detector, is described. Abstract : This paper describes a method for rapid measurements of the specular X‐ray reflectivity signal using an area detector and a monochromatic, well collimated X‐ray beam (divergence below 0.01°), combined with a continuous data acquisition mode during the angular movements of the sample and detector. In addition to the total integrated (and background‐corrected) reflectivity signal, this approach yields a three‐dimensional mapping of the reciprocal space in the vicinity of its origin. Grazing‐incidence small‐angle scattering signals are recorded simultaneously. Measurements up to high momentum transfer values (close to 0.1 nm −1, also depending on the X‐ray beam energy) can be performed in total time ranges as short as 10 s. The measurement time can be reduced by up to 100 times as compared with the classical method using monochromatic X‐ray beams, a point detector and rocking scans (integrated reflectivity signal).